Affective polarization in a Facebook group, between hateful subjectivities and populist agonisms. Case #Culiacanazo, Mexico - Iturralde Chaparro, Enrique (2025)
This article analyzes affective polarization in a Facebook group on public and historical issues. Through a critical discourse analysis of the 10 most engaged posts during a specific period, in which the "#Culiacanazo" (the failed operation to capture a drug trafficker during the Andrés Manuel López Obrador administration) was prominent on social media, it was found that affective content predominated over deliberative content. If for political science, polarization threatens liberal democracies, for post-Marxist perspectives, like populist agonism, they are also forms of political participation. This, in the context of Latin American countries, whose social complexity requires an understanding beyond bourgeois liberal rationality.